$$\int \frac{\sin^3\frac\theta 2}{\cos\frac\theta2 \sqrt{\cos^3\theta + \cos^2\theta + \cos\theta}} d\theta$$

My Attempt: $$I = \int \frac{\sin^2\frac\theta2\cdot\sin\frac\theta2\cos\frac\theta2}{\cos^2\frac\theta2 \sqrt{\cos^3\theta + \cos^2\theta + \cos\theta}} d\theta \\ = \frac12 \int \frac{(1-\cos\theta)\sin\theta}{(1+\cos\theta)\sqrt{\cos^3\theta + \cos^2\theta + \cos\theta}} d\theta$$ $$\text{let }\cos\theta = t \implies -\sin\theta d\theta = dt$$ $$I = \frac12 \int \frac{t-1}{(t+1) \sqrt{ t^3+t^2+t } } dt $$

I am not sure how to proceed further from here. Any hints/solutions on how to resolve the cubic expression under the square root?

  • 1
    $\begingroup$ take $t^2$ out of the denominator and then substitute $s= \frac{1}{t} + t$ you will see that the numerator will give $\textbf{d}s$ and this integral will be solvable by standard procedure. $\endgroup$ Jun 29 at 17:25

Use $s = \frac{t-1}{t+1} \implies t = \frac{1+s}{1-s}$

$$I = \frac{1}{2}\int \frac{2s}{\sqrt{3-2s^2-s^4}}\:ds = \frac{1}{2}\int\frac{2s}{\sqrt{4-(s^2+1)^2}}\:ds = \frac{1}{2}\sin^{-1}\left(\frac{s^2+1}{2}\right)$$

Then keep reversing the substitutions

$$I = \frac{1}{2}\sin^{-1}\left(\frac{\left(\frac{t-1}{t+1}\right)^2+1}{2}\right) = \frac{1}{2}\sin^{-1}\left(\frac{t^2+1}{(t+1)^2}\right)$$

$$\implies I = \frac{1}{2}\sin^{-1}\left[\frac{1}{4}\sec^4\left(\frac{\theta}{2}\right)-\tan^2\left(\frac{\theta}{2}\right)\right]+C$$


Set $\sqrt t=y,t=y^2,dt=2y\ dy$

$$I =\int\dfrac{(y^2-1)2y}{(y^2+1)y\sqrt{y^2(y^4+y^2+1)}}dy$$


Set $\int(1-1/y^2)dy =z$

Then $\sqrt{z^2+1}=u\implies z^2+1=u^2$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.